Risk assessment to reduce thromboembolic disease in obstetric practice: a regional audit. (18th April 2012) - Gherghe, M; Moss, H; Gibson, J; Brennand, J
Abstract : The documented performance and the accuracy of risk assessment for thromboembolic disease in obstetric practice was performed in 3 teaching hospitals within Greater Glasgow and Clyde. Auditable standards were prompted by RCOG Green-top Guideline No 37. 120 cases identified at the time of delivery provided the data for risk assessment at booking and postnatal care. 57 cases were identified at the time of antenatal discharge, providing data for antenatal inpatient assessments. Retrospective case note review provided the data. There was documented evidence of the performance of a thrombotic risk assessment in 10/120, 0/57 and 84/120 cases at booking, during admission and postpartum respectively. There was documented evidence of increased risk of VTE being assigned in 2/120, 0/57 and 70/120 cases at booking, admission and postpartum respectively. Risk was correctly assigned in 1/2 booking cases and 37/70 postnatal cases. Retrospective review demonstrated that 5/6 high risk and 8 intermediate risk cases were not identified at booking. Two high risk antenatal admissions and 6/9 high risk postnatal cases were not identified. 22 antenatal admissions and 23 postnatal cases were not identified as being intermediate risk. As a result high risk women were not prescribed, and intermediate risk women were not considered for or prescribed thromboprophylaxis. Of those women receiving heparin only 67% were prescribed an appropriate dose according to booking weight. An improvement in the performance of risk assessment for VTE is required in all areas of obstetric practice. The introduction of a new proforma to aid practice is required.